Implementasi Metode Pose To Pose Untuk Perancangan Animasi 2D Proses Pernikahan Adat Jawa - Muharram Martua Harahap (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2020)
The development of animation nowadays increasingly puts demands on animators to complete their work quickly. In this thesis, we will discuss about a method which will make it easier for animators to finish production without wasting time. Create a traditional Javanese wedding process with the Pose to Pose method. 2D animation that is influenced by a good animating process on its movements will make the animation look alive. The pode to pose technique is one of the methods used in the animating process because the application of this method uses the basic principles of animation. By using the pose to pose method, the resulting movement will be known. The method applied aims to smooth the motion in animation.Keywords: Animation, Pose To Pose Method, Marriage, Javanese Custom